Pseudo embryos. Intelligibility in the limit of our intelligence? - Besio Rollero, Mauricio (Acta Bioethica, 2012)
Scientific research has made possible new hopes for the cure of diverse pathologies provoked by degenerative processes or by direct damage on organs and tissues. One of the fields of study most promising is the use of pluripotential cells, being their main origin embryos obtained by assisted reproduction techniques. But, the ethical questioning with respect to their use and destruction has guided human talent to develop entities similar to embryos, but not essentially. If this were true, their use to obtain these valuable cells will not be ethically objectionable. These pseudo embryos challenge our intelligence to establish their true ontological statute. This article reflects about the difficulty in applying the different criteria that our intelligence uses to identify or not the presence of a human being with all his/her rights and dignity in a series of natural and created by man entities.